2019
DOI: 10.1021/acsami.9b05135
|View full text |Cite
|
Sign up to set email alerts
|

High-Adhesion Stretchable Electrode via Cross-Linking Intensified Electroless Deposition on a Biomimetic Elastomeric Micropore Film

Abstract: For the stretchable electrode, strong interface adhesion is the primary guarantee for long service life, and the maximization of the tensile limit with remarkable electrical stability can expand the scope of its use. Here, a cost-effective strategy is proposed to fabricate a high-adhesion stretchable electrode. By modifying dopamine and functionalized silane on a polydimethylsiloxane (PDMS) substrate in sequence before the electroless deposition process, super-high adhesion up to 3.1 MPa is achieved between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 77 publications
0
24
0
Order By: Relevance
“…Similarly, Wu et al demonstrated that an Ag layer plated on the biomimetic microporous elastomer substrate exhibited a strong adhesion (3.1 MPa) at the interface and showed a large tensile limit strain exceeding = 70%. [163] The microporous structure regularly adjusted the strain distribution and prevented the formation of large cracks while being stretched. The microstructured interface was also used for making robust electrode/electrolyte interface in the stretchable supercapacitor.…”
Section: Strong Interfacial Adhesion In Microstructured Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Wu et al demonstrated that an Ag layer plated on the biomimetic microporous elastomer substrate exhibited a strong adhesion (3.1 MPa) at the interface and showed a large tensile limit strain exceeding = 70%. [163] The microporous structure regularly adjusted the strain distribution and prevented the formation of large cracks while being stretched. The microstructured interface was also used for making robust electrode/electrolyte interface in the stretchable supercapacitor.…”
Section: Strong Interfacial Adhesion In Microstructured Surfacementioning
confidence: 99%
“…Introducing buckling, islands, or high relief structures into the interfaces could adjust the strain applied to the two different layers. [ 142–161 ] The adhesion between the two layers was increased by introducing microstructured surfaces at the interfaces, [ 142–166 ] such as interlocking metal nanopiles, [ 162 ] hydrogels, [ 164 ] and SBS block copolymers. [ 165,166 ] Interfacial adhesion between the multiple device components is an important issue for integrated stretchable devices.…”
Section: Design Of Mesoscale Interfacesmentioning
confidence: 99%
“…[ 5a ] The well‐known methods for fabricating CNT‐based flexible conductive devices include spray coating [ 9 ] and mixing. [ 4b,10 ] However, these processes currently have several drawbacks. While the direct spray coating method offers high conductivity, it is difficult to fabricate a stretchable electrode, because the CNT electrode is easily damaged by continuous tensile or external contact.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible tactile sensors are widely used in electronic skin [ 1 , 2 , 3 ], robots [ 4 , 5 , 6 ], wearable devices [ 7 , 8 , 9 ], etc. Depending on the source of the signal, the tactile sensors are classified into capacitive-type [ 10 , 11 ], piezoelectric-type [ 12 , 13 ], triboelectric-type [ 14 ] and piezoresistive-type [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%